2018
DOI: 10.15252/embj.201899134
|View full text |Cite
|
Sign up to set email alerts
|

Acidic cell elongation drives cell differentiation in the Arabidopsis root

Abstract: In multicellular systems, the control of cell size is fundamental in regulating the development and growth of the different organs and of the whole organism. In most systems, major changes in cell size can be observed during differentiation processes where cells change their volume to adapt their shape to their final function. How relevant changes in cell volume are in driving the differentiation program is a long-standing fundamental question in developmental biology. In the root meristem, characteristic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 23 publications
8
89
1
Order By: Relevance
“…Cytokinin concentrations were developmentally driven as the positive correlation between total cytokinin concentration and fruit weight held true also within each treatment, in agreement with Pilkington et al [15]. Further experimentation will be required to clarify the mechanism and if, similar to Arabidopsis roots, the signalling may be mediated by a type-B RR [44].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Cytokinin concentrations were developmentally driven as the positive correlation between total cytokinin concentration and fruit weight held true also within each treatment, in agreement with Pilkington et al [15]. Further experimentation will be required to clarify the mechanism and if, similar to Arabidopsis roots, the signalling may be mediated by a type-B RR [44].…”
Section: Discussionsupporting
confidence: 80%
“…A meta-analysis of cytokinin effects on Arabidopsis transcriptome identified expansins as targets of cytokinin signalling [43]. Expansins drive acidic cell elongation in Arabidopsis roots, where α-expansinA genes and plasma membrane H(+)-ATPase are controlled by cytokinins via ARR1 [44]. In soybean, cytokinins regulate the expression of expansin and cell wall expansion [45].…”
Section: Discussionmentioning
confidence: 99%
“…The growth of plant cells is in tight relationship with cell wall loosening, which can be mediated by expansins. Recently, interplay between CK and expansin in root development has been reported (Pacifici et al ., ). These authors suggested that ARR1 stimulates EXPA1‐driven cell wall loosening and consequent cell elongation in Arabidopsis roots.…”
Section: Discussionmentioning
confidence: 97%
“…EXPA1 was reported to be induced by cytokinin in the root, which is involved in controlling cell differentiation initiation (Bhargava et al ., ; Pacifici et al ., ). Interestingly, the development of root hairs was delayed in the expa1 mutant, indicating a setback in cell differentiation (Pacifici et al ., ). These data support the hypothesis that EXPA1 could be connected to the root hair phenotype of AtERF#111‐OE plants.…”
Section: Discussionmentioning
confidence: 97%